Connecting economic impact of cassava diseases: CBSD as a major threat from Sub-Saharan Africa to Southeast Asia - Reyes, Byron; Esponda, Maria Del Mar; Schiek, Benjamin; Petsakos, Athanasios; Andrade, Robert (2025)
Understanding cassava diseases like CBSD from a cross-regional perspective is essential, as the lack of investment in preventive breeding pipelines in Southeast Asia—despite the availability of resistant genetic accessions in Latin America and the devastating precedent in Africa—leaves the region vulnerable to future outbreaks that could cost millions, highlighting the critical need for proactive, globally informed R&D strategies.